High-thermal-conductivity graphene fiber and resin composite material and preparation method thereof

Through high-temperature graphitization treatment and modification of graphene fiber and resin composite materials, the problem of insufficient thermal conductivity of traditional carbon fibers is solved, and the high thermal conductivity and good interface performance of graphene fiber/resin composite materials are achieved.

CN119859379APending Publication Date: 2025-04-22SHAOXING RES INST OF ZHEJIANG UNIV

Patent Information

Application Number
CN202411428166.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Traditional carbon fibers have difficulty in making breakthrough progress in electrical and thermal conductivity, and the degree of interface bonding between graphene fibers and resin composite materials is insufficient, which affects its performance.

Method used

Graphene fibers treated with high temperature graphitization are used, and the interfacial and thermal conductivity of the composite material are improved by modifying graphene fibers or thermosetting resins. Specific methods include wet spinning process to prepare graphene fibers, undergo chemical reduction and high-temperature graphitization, followed by sizing and hot pressing processes to enhance interface bonding.

Benefits of technology

The high thermal conductivity and good interfacial performance of the composite material in the parallel fiber direction are achieved, simplifying the preparation process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859379A_ABST
    Figure CN119859379A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene fiber and resin composite material with high thermal conductivity. The graphene fiber and resin composite material comprises continuous graphene fiber filaments, wherein the surfaces of the continuous graphene fiber filaments are coated with a sizing agent; the surface of the graphene fiber is coated with the modified epoxy resin; the preparation method comprises the following steps: preparing continuous and uniform graphene oxide fiber filaments through a wet spinning technology; fully reducing the graphene oxide fiber through a chemical reduction method; performing graphitization treatment on the graphene oxide fiber subjected to chemical reduction at ultrahigh temperature to obtain graphene fiber; then the graphene fiber laying layer is put into a mold coated with demolding wax, each layer of fiber is fixed with epoxy resin, and demolding cloth covers the graphene fiber laying layer after the graphene fiber laying layer is finished and is used for demolding and absorbing redundant resin; the graphene fiber / resin composite material prepared by the preparation method disclosed by the invention not only has good heat-conducting property, but also has relatively good interface property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of composite materials, and in particular to a high thermal conductivity graphene fiber and resin composite material and a preparation method thereof. Background Art

[0002] Graphene is a special material with a unique nano-scale carbon atom single-layer arrangement structure, and has excellent performance in many fields such as mechanics, thermal, electrical and optical. Graphene fiber (GF) is a one-dimensional continuous fiber material formed by the orderly arrangement and assembly of single-layer graphene along the axial direction. It is a new type of carbon fiber material. Graphene fiber inherits many advantages of graphene and has good electrical conductivity, thermal conductivity and mechanical properties. From the perspective of elemental composition, both graphene fiber and carbon fiber are composed of pure carbon atoms, but the crystallinity and orientation of graphene fiber are better than carbon fiber, so the former may be better than carbon fiber in terms of electrical conductivity, thermal conductivity and mechanical properties. At present, high thermal conductivity carbon fiber has been widely used in high-tech fields such as textiles, aerospace, construction, and electronics due to its advantages such as good mechanical strength, electrical conductivity, thermal conductivity and electromagnetic shielding performance along the axial direction. In addition, combining carbon fibers by weaving can not only obtain carbon fiber reinforced fabrics, but also compound them with resins to make carbon fiber / resin reinforced composite materials, which greatly broadens the application scenarios of carbon fibers.

[0003] Generally speaking, the higher the crystallinity of carbonaceous materials and the larger the size of the crystal region, the higher the efficiency of electron and phonon transfer, and the better the electrical and thermal properties. However, the preparation of traditional carbon fibers generally uses small molecule asphalt or high molecular weight polyacrylonitrile as raw materials, and forms a nano-scale turbostratic graphite structure after high-temperature heat treatment. These turbostratic graphite regions are too small in size, causing electrons and phonons to scatter at their edges. Therefore, it is difficult for traditional carbon fibers to achieve breakthrough progress in electrical and thermal conductivity. Graphene oxide fibers are prepared by wet spinning of large-sized single-layer graphene oxide, and then chemically reduced and ultra-high temperature graphitized to obtain graphene fibers with an ordered crystal region structure, which can achieve excellent thermal and electrical conductivity.

[0004] However, studies have shown that the surface of graphene fibers lacks polar groups, and its surface inertness is large and the surface energy is low. When used as a composite reinforcement, the degree of interfacial bonding with the resin matrix is ​​difficult to meet actual needs. Therefore, it is necessary to surface treat the graphene fibers, and the methods for fiber surface treatment include electrodeposition, gas / liquid phase oxidation, grafting, coating, etc. Surface treatment is beneficial to increase the surface activity of the fibers and to improve the performance of graphene fiber / resin composites. At present, the research on carbonaceous fiber composites mainly focuses on asphalt-based and polyacrylonitrile-based carbon fibers, and there is little research on graphene fiber-based composites. Replacing traditional carbon fibers with graphene fibers can effectively improve the thermal conductivity of composite materials. Therefore, how to study a graphene fiber / resin composite material with high thermal conductivity is a problem that needs to be solved at this stage. In response to the above problems, a solution is proposed below. Summary of the invention

[0005] The purpose of the present invention is to provide a high thermal conductivity graphene fiber and resin composite material and a preparation method thereof, which has the advantages of enhancing the interface performance of the composite material and having good thermal conductivity.

[0006] The above technical objectives of the present invention are achieved through the following technical solutions: A high thermal conductivity graphene fiber and resin composite material comprises graphene fibers and resin, wherein the graphene fibers are prepared by a wet spinning process, the graphene fibers are in filament form, the resin is a thermosetting resin, and the thermosetting resin covers the surface of the graphene fiber bundle to form a resin layer; the graphene fibers are laid in different arrangement forms; the thickness of the resin layer is 80 to 150 μm; and the diameter of the graphene fibers is 15 to 25 μm.

[0007] Preferably, at least one of the graphene fiber and the thermosetting resin is modified: the modified graphene fiber is a graphene fiber surface treated with a sizing grade; the modified thermosetting resin is modified with a high thermal conductivity nanomaterial.

[0008] Preferably, the high thermal conductivity nanomaterial is one of carbon nitride g-C3N4, carbon nanotube CNT, Mxene, and transition metal oxide; the size of the high thermal conductivity nanomaterial is 200-500 nm; and the thermosetting resin is epoxy resin.

[0009] As a preference, the method comprises the following steps: S1: placing the graphene fiber obtained by the wet spinning process in a mixed solution of hydroiodic acid and acetic acid for reaction, and after the reaction is completed, repeatedly rinsing with ethanol and deionized water until the washing liquid is colorless; placing the fully reduced graphene fiber in a vacuum environment to fully remove the reducing agent and the reduction product; and finally obtaining chemically reduced graphene oxide fiber; S2: The graphene fibers obtained above are subjected to heat treatment, first using a hydrogen-argon mixed gas ( ) replace the air in the tube for more than 3 times; then put the graphene fiber into a tubular furnace, heat it to different target temperatures, keep it for a certain period of time, then cool it to room temperature, and take it out to obtain graphene fibers with different reduction temperatures; S3: immersing the thermally reduced graphene fibers obtained above into an ethanol solution for fiber spreading, and cleaning the broken fibers and nodules in the graphene fiber bundles during the fiber spreading process; placing the treated graphene in an oven for complete drying; S4: placing the completely dried graphene fiber bundle obtained above in a sizing tank containing a sizing agent, so that the sizing agent completely immerses the graphene fiber bundle, and passing through upper and lower squeezing rollers at a speed of 0.05 m / s to squeeze out excess sizing agent; and completely drying the sized graphene fibers at room temperature; S5: Cut the sizing graphene fibers obtained above into appropriate lengths, straighten and tighten them and lay them flat in a mold, and fix each layer of graphene fibers with epoxy resin; after they are completely cured, demould and cut them into required sizes to obtain the graphene fiber / resin-based composite material; S6: When the hot pressing process is adopted, the sizing graphene fiber bundles obtained above are laid in a mold, and the diluted epoxy resin is poured into the graphene mold to completely infiltrate the fibers, and the fibers are placed in a vacuum oven to dry; then the fibers are treated with a hot pressing process, and after they are completely cured, they are demolded and cut into the required size to obtain a graphene fiber / resin composite material.

[0010] Preferably, in step S1, the mass ratio of hydroiodic acid to acetic acid is 1:3; and the temperature of the vacuum drying oven is set to 90°C.

[0011] Preferably, in step S2, the heating rate of the tubular furnace is 2-5°C / min; the temperature is 2800-3000°C.

[0012] Preferably, in step S5, the epoxy resin and the curing agent are mixed in a mass ratio of 1:1, stirred for 15 minutes, and degassed in a vacuum environment.

[0013] Preferably, in step S5, the resin and ethanol are mixed in a mass ratio of 1:4 and stirred for 10 min.

[0014] Preferably, the laying methods of the graphene fibers in step S5 include single longitudinal arrangement, alternating horizontal and vertical "well" arrangement, and "rice" arrangement.

[0015] Preferably, the epoxy resin is a low-temperature curing epoxy resin; the curing temperature of the medium-temperature curing epoxy resin is 30-100° C.; the preparation method of the epoxy resin includes a hot pressing method or a vacuum bag method.

[0016] The beneficial effects of the present invention are: The present invention uses graphene fibers that have been subjected to high-temperature graphitization treatment to replace traditional carbon fibers, and directly modifies epoxy resin or directly modifies graphene fibers to improve the interface performance and thermal conductivity of graphene fiber / resin composite materials. The prepared composite material has good interface performance and high thermal conductivity in the direction parallel to the fibers. The preparation method of the composite material of the present invention is simple and cost-effective. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The front, side and back structural diagrams of the graphene fiber / epoxy resin composite material prepared in Example 1; Figure 2 (a) is a SEM image of the graphene fiber obtained after high-temperature graphitization in Example 1; Figure 2 (b) is a SEM image of the graphene fiber after sizing treatment in Example 1; Figure 2 (c) is a SEM image of the cross section of the graphene fiber / resin composite material prepared by the vacuum bag method in this embodiment; Figure 3 The stress-strain spectrum of the composite material prepared in Example 1 when different numbers of graphene fibers are laid in a single longitudinal direction; Figure 4 The thermogravimetric analysis spectra of the graphene fiber, epoxy resin, and graphene fiber / resin composite material prepared in Example 1. DETAILED DESCRIPTION

[0018] The following is only a preferred embodiment of the present invention, and the protection scope is not limited to this embodiment. All technical solutions under the concept of the present invention should belong to the protection scope of the present invention. The same parts are represented by the same reference numerals.

[0019] Example 1 This embodiment is a specific implementation of the present invention, which specifically includes the following steps: Graphene oxide was dispersed in deionized water, mechanically stirred vigorously for 24 h, and then ultrasonically treated for 6 h to obtain a graphene oxide dispersion, which was used as a spinning solution. The solid content in the spinning solution was 5 mg ml-1. The prepared spinning solution was transferred to a syringe with a capacity of 10 ml. The head of the syringe was connected to a PEEK spinning tube with an inner diameter of about 300 μm, and the other end of the spinning tube was placed in a CaCl2 coagulation bath with a concentration of 10 mg ml-1. The coagulated fiber was connected to a drawing device, and a collection roller with a speed of 100 rpm min-1 was connected after the drawing device. The gel fiber after drawing was collected on the roller. After spinning, the fiber was removed and dried at 60°C for 12 h. The dried fiber was placed in a tubular furnace in a N2 atmosphere at 800°C for 2 h, and naturally cooled to room temperature to obtain graphene oxide fiber. The above-prepared graphene oxide fiber is placed in a mixed solution of hydroiodic acid and acetic acid in a mass ratio of 1:3, chemically reduced at 90°C for 2 h, repeatedly rinsed with ethanol and deionized water, and dried to obtain chemically reduced graphene fiber. The chemically reduced graphene oxide fiber prepared in the previous step is placed in a tubular furnace, and then heated from room temperature to 1600°C at a heating rate of 5°C min-1, kept for 1 h, and then naturally cooled to room temperature to obtain heat-treated graphene fiber. The above-mentioned heat-treated graphene fiber is placed in a high-temperature graphitization furnace, the gas is replaced twice with ultrapure argon, and then the temperature is increased to 2800°C at a rate of 10°C min-1 and kept for 2h. When the furnace body is cooled to room temperature, high-temperature graphitized graphene fiber can be obtained.

[0020] The graphene fibers are immersed in an ethanol solution for fiber spreading. During the fiber spreading process, the graphene fiber bundles are combed with a comb to remove broken fibers and nodules in the graphene fiber bundles. The treated graphene fiber bundles are placed in an oven for complete drying. The completely dried graphene fiber bundles obtained above are passed through a tank containing a sizing agent at a speed of 0.5 mm / s, so that the sizing agent completely immerses the graphene fiber bundles, and pass through upper and lower extrusion rollers at a uniform speed to squeeze out excess sizing agent, and the sizing graphene fibers are completely dried at room temperature. The demoulding wax is evenly applied to the surface of the PTFE mold, and the demoulding wax is completely atomized on the surface of the mold. This process is repeated 3 times, and then the epoxy resin and the curing agent are mixed in a mass ratio of 1:1, stirred for 15 min, and vacuum treated at 80°C for 10 min for degassing. The mixed resin is mixed and diluted with ethanol in a mass ratio of 1:4, and then the resin is evenly applied to the surface of the mold, and the graphene fibers are evenly layered in the mold, and each layer of graphene fibers is connected and fixed with resin. After the layering is completed, the top layer is covered with a release cloth to absorb excess resin, and the release cloth is covered with a breathable felt. The treated materials are placed in an oven at 60°C for 30 min, and then the materials are placed in a vacuum bag, which is evacuated to a vacuum and fixed at room temperature for 12 h. After curing, it is taken out and cut into a suitable size to obtain a high thermal conductivity graphene fiber composite material.

[0021] like Figure 1 As shown, the composite material presents a sheet-like solid structure, the morphology of the back side is derived from the checkered pattern of the release cloth, and the thickness of the composite material is changed by using different numbers of layers of graphene for lamination.

[0022] Figure 2 (a) is a SEM photograph of the graphene fiber obtained after high-temperature graphitization in this example. The graphene fiber exhibits a uniform and continuous fiber structure, and the fiber surface is wrinkled, which is a unique structure of flake graphene. Figure 2 (b) is a SEM photograph of the graphene fiber of this embodiment after sizing treatment, which still maintains a continuous fiber shape and the fiber surface is evenly coated with granular substances. Figure 2 (c) is a SEM photograph of the cross section of the graphene fiber / resin composite material prepared by the vacuum bag method in this embodiment. It can be seen that the graphene fibers are uniformly embedded in the resin matrix, the interface performance between the graphene and the resin is good, and the fibers and the resin are tightly bonded.

[0023] like Figure 3As shown in the figure, the graphene fiber / resin composites exhibit tensile-strain properties, and all the composites show high tensile strain. In addition, the tensile-strain properties of the composites show an enhancing trend with the increase in the number of graphene fiber layers. The composite containing 5 layers of graphene fibers has a tensile stress of 102.3 MPa and a strain of 26.2%, indicating that the combination of graphene fibers and resin gives the composites good mechanical properties.

[0024] like Figure 4 As shown in the figure, the thermal decomposition temperature of epoxy resin is the lowest, which is 140°C; the thermal decomposition temperature of graphene fiber is 348°C; the thermal decomposition temperature of the composite material is between the two, reaching 169°C. In addition, after being compounded with graphene fiber, the carbon residue of epoxy resin increased from 5.79% to 14.59%, indicating that the thermal decomposition rate of the composite material decreased.

[0025] The composite material has high thermal conductivity in the direction parallel to the fiber plane and can effectively resist external heat sources.

[0026] Example 2 This embodiment is a specific implementation of the present invention, which specifically includes the following steps: Prepare chemically reduced graphene fibers in the same manner as in Example 1, place the chemically reduced graphene oxide fibers in a tubular furnace, then heat them from room temperature to 1600°C at a heating rate of 5°C min-1, keep them for 1 hour, and then naturally cool them to room temperature to obtain heat-treated graphene fibers. Place the heat-treated graphene fibers in a high-temperature graphitization furnace, replace the gas twice with ultrapure argon, then heat them to 3000°C at a rate of 10°C min-1 and keep them for 2 hours, and wait for the furnace to cool to room temperature to obtain high-temperature graphitized graphene fibers. Immerse the graphene fibers in an ethanol solution for filament spreading, comb the graphene fiber bundles with a comb during the filament spreading process to remove broken fibers and nodules in the graphene fiber bundles; place the treated graphene fiber bundles in an oven to completely dry. The completely dried graphene fiber bundle obtained above is placed in a tank containing a sizing agent, so that the sizing agent completely immerses the graphene fiber bundle, and passes through upper and lower squeezing rollers at a uniform speed to squeeze out excess sizing agent, and the sized graphene fibers are completely dried at room temperature.

[0027] Subsequently, the epoxy resin and the curing agent were mixed in a mass ratio of 1:1, stirred for 15 min and vacuum treated at 80°C for 10 min for degassing. The mixed resin was mixed and diluted with ethanol in a mass ratio of 1:4 to obtain a diluted epoxy resin. The sizing graphene fiber obtained above was straightened and tightened, passed through a tank containing epoxy resin at a speed of 0.5 mm / s, and passed through the upper and lower extrusion rollers at a uniform speed to squeeze out excess epoxy resin, and the graphene fiber prepreg was evenly laid in the mold, and the fiber content in the composite material was increased by increasing the number of fiber layers. After the layering was completed, all the materials were placed in an oven at 60°C for 30 min, then taken out and covered with a demoulding cloth on the top layer to absorb excess resin, and placed in a hot press, and hot-pressed and cured at 130°C for 2 hours at a pressure of less than 2 MPa. After the hot pressing was completed, the demoulding was taken out to obtain a graphene fiber and epoxy resin composite material.

[0028] In this embodiment, hot pressing is used as a molding process for the composite material. The composite material obtained by hot pressing has a significantly increased volume fraction and mass fraction of graphene fibers at the same volume. The increase in fiber mass can significantly increase the out-of-plane thermal conductivity of the composite material. In addition, hot pressing curing makes the arrangement of fibers in the composite material more compact, further improving the interface performance of the composite material.

[0029] Since there are many embodiments of the present invention, the experimental data of each embodiment is huge and numerous, which is not suitable for listing and explaining one by one here, but the contents required to be verified and the final conclusions obtained in each embodiment are similar. Therefore, the verification contents of each embodiment are not explained one by one here, and only implementation 1 and 2 are used as representatives to illustrate the excellence of the present invention.

[0030] The specific embodiments described above further illustrate the technical problems, technical solutions and beneficial effects solved by the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high thermal conductivity graphene fiber and resin composite material, comprising graphene fiber and resin, characterized in that: The graphene fibers are prepared by a wet spinning process, the graphene fibers are in filament form, the resin is a thermosetting resin, and the thermosetting resin covers the surface of the graphene fiber bundle to form a resin layer; the graphene fibers are laid in different arrangement forms; the thickness of the resin layer is 500 to 600 μm; and the diameter of the graphene fibers is 15 to 25 μm.

2. The high thermal conductivity graphene fiber and resin composite material according to claim 1, characterized in that: At least one of the graphene fiber and the thermosetting resin is modified: the modified graphene fiber is a graphene fiber surface treated with a sizing level; the modified thermosetting resin is modified with a high thermal conductivity nanomaterial.

3. The high thermal conductivity graphene fiber and resin composite material according to claim 2, characterized in that: The high thermal conductivity nanomaterial is one of carbon nitride g-C3N4, carbon nanotube CNT, Mxene, and transition metal oxide; the size of the high thermal conductivity nanomaterial is 200-500 nm; and the thermosetting resin is epoxy resin.

4. A method for preparing a high thermal conductivity graphene fiber and resin composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: placing the graphene fiber obtained by the wet spinning process in a mixed solution of hydroiodic acid and acetic acid for reaction, and after the reaction is completed, repeatedly rinsing with ethanol and deionized water until the washing liquid is colorless; placing the fully reduced graphene fiber in a vacuum environment to fully remove the reducing agent and the reduction product; and finally obtaining chemically reduced graphene oxide fiber; S2: The graphene fibers obtained above are subjected to heat treatment, first using a hydrogen-argon mixed gas ( ) replace the air in the tube for more than 3 times; then put the graphene fiber into a tubular furnace, heat it to different target temperatures, keep it for a certain period of time, then cool it to room temperature, and take it out to obtain graphene fibers with different reduction temperatures; S3: immersing the thermally reduced graphene fibers obtained above into an ethanol solution for fiber spreading, and cleaning the broken fibers and nodules in the graphene fiber bundles during the fiber spreading process; placing the treated graphene in an oven for complete drying; S4: placing the completely dried graphene fiber bundle obtained above in a sizing tank containing a sizing agent, so that the sizing agent completely immerses the graphene fiber bundle, and passing through upper and lower squeezing rollers at a speed of 0.05 m / s to squeeze out excess sizing agent; and completely drying the sized graphene fibers at room temperature; S5: Cut the sizing graphene fibers obtained above into appropriate lengths, straighten and tighten them and lay them flat in a mold, and fix each layer of graphene fibers with epoxy resin; after they are completely cured, demould and cut them into required sizes to obtain the graphene fiber / resin-based composite material; S6: When the hot pressing process is adopted, the sizing graphene fiber bundle obtained above is completely immersed in a tank containing resin and passed through upper and lower extrusion rollers at a speed of 0.05 m / s to squeeze out excess resin; the prepreg is straightened and laid flat in the mold; after being completely cured, it is demoulded and cut into the required size to obtain a graphene fiber / resin composite material.

5. The high thermal conductivity graphene fiber and resin composite material and the preparation method thereof according to claim 4, characterized in that: In step S1, the mass ratio of hydroiodic acid to acetic acid is 1:3; and the temperature of the vacuum drying oven is set to 90°C.

6. The high thermal conductivity graphene fiber and resin composite material and the preparation method thereof according to claim 4, characterized in that: In step S2, the heating rate of the tubular furnace is 2-5°C / min; the temperature is 2800-3000°C.

7. The high thermal conductivity graphene fiber and resin composite material and the preparation method thereof according to claim 4, characterized in that: In step S5, the epoxy resin and the curing agent are mixed in a mass ratio of 1:1, stirred for 15 minutes, and degassed in a vacuum environment.

8. The high-temperature graphene fiber and resin composite material and the preparation method thereof according to claim 4, characterized in that: In the step S5, the mixed resin is diluted according to a mass ratio of resin to ethanol of 1:4, and stirred for 10 minutes.

9. The high thermal conductivity graphene fiber and resin composite material and the preparation method thereof according to claim 4, characterized in that: The laying methods of the graphene fibers in step S5 include single longitudinal arrangement, alternating horizontal and vertical "well" arrangement, and "rice" arrangement.

10. The high thermal conductivity graphene fiber and resin composite material and the preparation method thereof according to claim 4, characterized in that: The epoxy resin is a low-temperature curing epoxy resin; the curing temperature of the medium-temperature curing epoxy resin is 30-100° C.; the preparation method of the epoxy resin includes a hot pressing method or a vacuum bag method.

Citation Information

Patent Citations

  • Graphene oxide fiber, preparation method, and preparation method of graphene oxide fiber composite material

    CN103396586A

  • Fiber wave-absorbing material

    CN106751456A

  • Manufacturing process for glass fiber-reinforced plastic product

    CN108773089A

  • Graphene fiber, mold, graphene fiber reinforced heat-conducting gasket and preparation method of graphene fiber reinforced heat-conducting gasket

    CN114800989A

  • Vinyl ester pultrusion composite material and process

    CN118165469A

Cited By

  • Sizing method of graphene fiber

    CN121451436A

  • A sizing method for graphene fibers

    CN121451436B

  • Two-step sizing process for graphene fibers

    CN121473135A

  • A two-step sizing process for graphene fibers

    CN121473135B